Manajemen Strategi Pengembangan Bumdes Sebagai Sarana Penambahan Dana Desa di Desa Pandan Wangi Kecamatan Jerowaru - Heri Adi Saputra; Juliadi; Syahdan (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Village-owned enterprises (BUMDes) have become an important instrument in improving the economy of village communities in Indonesia, especially in Pandan Wangi Village. One of the main roles of BUMDes is as a means of increasing village funds through various appropriate development strategies. This research aims to analyze the strategic management of BUMDes development to increase Pandan Wangi Village funds at the local level. This research uses qualitative methods by conducting in-depth interviews with BUMDes managers as well as documentation studies related to managing BUMDes development strategies as a means of increasing village funds, including Business diversification, marketing local products, developing collaboration with external parties, and strengthening internal management of BUMDes. By implementing these strategies, BUMDes can become a motor for sustainable local economic development and significantly contribute to increasing village funds. It is hoped that this research can provide input for BUMDes managers, the Regional Government, and related parties in developing BUMDes as a solution to improving the welfare of the Pandan Wangi Village Community.